The role of the vagus nerve in fibromyalgia syndrome. (December 2021) - Martins, Daniel F.; Viseux, Frederic J.F.; Salm, Daiana C.; Ribeiro, Anny Caroline Avelino; da Silva, Helen Kassiana Lopes; Seim, Lynsey A.; Bittencourt, Edsel B.; Bianco, Gianluca; Moré, Ari Ojeda Ocampo; Reed, William R.; Mazzardo-Martins, Leidiane
Highlights: Vagal dysfunction is present in fibromyalgia. Fibromyalgia is a stress-related disorder. Psychosocial factors can play an important role in fibromyalgia. Stress systems alter neurotransmitters in fibromyalgia. Abstract: Fibromyalgia (FM) syndrome is a common illness characterized by chronic widespread pain, sleep problems, fatigue, and cognitive difficulties. Dysfunctional neurotransmitter systems that influence the body's endogenous stress response systems are thought to underlie many of the major FM-related symptoms. A model of FM pathogenesis suggests biological and psychosocial variables interact to influence the genetic predisposition, but the precise mechanisms remain unclear. The Polyvagal Theory provides a theoretical framework from which to investigate potential biological mechanisms. The vagus nerve (VN) has anti-inflammatory properties via its afferent and efferent fibers. A low vagal tone (as assessed by low heart rate variability), has been observed in painful and inflammatory diseases, including FM, while the ventral branch of the VN is linked to emotional expression and social engagement. These anti-inflammatory and psychological (limbic system) properties of the VN may possess therapeutic potential in treating FM. This review paper summarizes the scientific literature regarding the potential role of the VN in transducing and/or therapeutically managing FM signs and symptoms.